Evaluation of recombinant factor C assay for the detection of divergent lipopolysaccharide structural species and comparison withLimulusamebocyte lysate‐based assays and a human monocyte activity assay. Issue 7 (July 2017) - Abate, Wondwossen; Sattar, Anas A.; Liu, Jian; Conway, Myra E.; Jackson, Simon K.
Abstract : Purpose. : The Limulus amebocytelysate (LAL) assay is widely used for the screening of lipopolysaccharide (LPS) in parenteral pharmaceuticals. However, correlation of LPS in Gram‐negative bacterial infections by LAL assay has been problematic, partly due to the variable reactivity of different LPS structures. Recombinant factor C (rFC) has allowed the development of a new simple, specific and sensitive LPS detection system (PyroGene). In this work, the potential of the new assay for detecting various LPS structures has been investigated and compared with two LAL‐based assays and a human monocyte activity assay. Methodology. : The activity of the various LPS structures has been investigated by PyroGene and two LAL‐based assays and a human monocyte activity assay. Results. : The rFC assay detected most LPS structures in picogram quantities and the potency of E. coli, B. cepacia, Salmonella smooth and Salmonella R345 LPS was no different when measured with PyroGene or LAL assays. However, the reactivity of K. pneumoniae, S. marcescens, B. pertussis and P. aeruginosa LPS differed significantly between these assays. Importantly, pairwise correlation analysis revealed that only the PyroGene assay produced a significant positive correlation with the release of IL‐6 from a monocytic cell line. Conclusion. : We conclude that the rFC‐based assay is a good replacement for conventional LAL assays and as it correlates significantly with IL‐6 produced by a human monocyte cell line it could potentially be more useful for detecting LPS in a clinical setting.